Autism spectrum disorder in Qatar: Profiles and correlates of a large clinical sample. (March 2017) - Alshaban, Fouad; Aldosari, Mohammed; El Sayed, Zakaria; Tolefat, Mohammed; El Hag, Saba; Al Shammari, Hawra; Ghazal, Iman; Fombonne, Eric
Autism spectrum disorder (ASD) is an increasingly prevalent disorder. Although around 15% of cases are caused by specific genetic causes, most cases involve a complex and variable combination of genetic risk and environmental factors that are not yet identified. There is a paucity of studies on ASD in Qatar, mostly in the form of case reports and genetic causes. The current study was designed to describe the clinical characteristics of ASD and its correlates in Qatar. Individuals with ASD were recruited from the Shafallah Center for Children with Special Needs which is the largest special needs center in Qatar. Within the sample of 171 individuals with ASD, 47% were ethnic Qataris, while 53% were nonethnic Qataris (Arabs and other nationalities). The analysis included the following factors: nationality, age, gender, socioeconomic status, consanguinity, prenatal/postnatal complications, and comorbidities. Eighty percent of the identified cases were males, with a 4:1 male to female ratio. Additionally, 83% of the families had one proband, 9.9% with 2 probands, and 7.1% with more than two. Comorbid conditions included: intellectual disabilities (ID) in 83% and epilepsy in 18.8%. 76.6% of subjects were nonverbal. There were 3 (1.8%) children with Rett's syndrome, 3 (1.8%) with Fragile X, and 1 (0.6%) with tuberous sclerosis. There are currently no publications that clarify the mean age of diagnosis in Qatar, however, the present study showed that more than half of the diagnosed cases were among the ages of 7–14 years (56%). The effect of consanguinity as a risk factor was not found to be significant.